2012
DOI: 10.1080/09296174.2012.714531
|View full text |Cite
|
Sign up to set email alerts
|

Model generation for word length frequencies in texts with the application of Zipf's order approach

Abstract: In the present paper we attempted to generate a parametric model for word frequencies.In order to make this relation applicable, we arranged word lengths in accordance with their normalized frequencies. The pattern of occurrence of words containing different numbers of letters has been investigated on the basis of their Zipf's order and by applying power law for Zipf's order and frequencies. The applicability of the generated mathematical model for word length frequencies was verified for different texts. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We expect that items which are frequently used are both short and stable. It is well known that there is a tendency for an inverse, nonlinear relationship between word length and frequency [36][37][38][39][40][41][42][43][44]. Additionally, it has been observed that more frequent words tend to be less often replaced in the evolution of languages [45][46][47].…”
Section: Stability Across Itemsmentioning
confidence: 99%
“…We expect that items which are frequently used are both short and stable. It is well known that there is a tendency for an inverse, nonlinear relationship between word length and frequency [36][37][38][39][40][41][42][43][44]. Additionally, it has been observed that more frequent words tend to be less often replaced in the evolution of languages [45][46][47].…”
Section: Stability Across Itemsmentioning
confidence: 99%
“…We expect that items which are frequently used are both short and stable. It is well known that there is a tendency for an inverse, nonlinear relationship between word length and frequency [36][37][38][39][40][41][42][43][44]. Additionally, it has been observed that more frequent words tend to be less often replaced in the evolution of languages [45][46][47].…”
Section: Stability Across Itemsmentioning
confidence: 99%
“…Much research has been done on word-length distribution (WLD) in different languages [22][23][24][25][26][27][28]. e frequency distribution of words with different lengths would not be chaotic but follow specific rules.…”
Section: Introductionmentioning
confidence: 99%